(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the present paper a definition, a model for building of MEMS (micro-electromechanical systems), types, their advantages and disadvantages have been given. The elements and the components, from which they are built, the development and the prediction of market about them have been considered as well more important firms, that manufacture them. A classification of MEMS is made on the basis of their designation and the region, where they operate. A special place is separated on the application of MEMS in the ecology as well as concrete examples are indicated – developments of firms and own ones.